PENGANTAR UJI STABILITAS UNTUK MODEL KOMPETISI ANTARA DUA POPULASI - Warsiki, Endang; Parhusip, Hanna Arini (MATEMATIKA, 2005)
The stability analysis for a competition model between two populations is the main topic in this paper. Stability is studied by considering theÂ eigenvalues of system differential equations according to the logistic equations which are developed for two populations. This paper can also be used as an introduction of the qualitative theory through a stability analysis. Additionally, this paper is proposed to the beginners in differential equations. Â